“Misi dan Strategi Gereja: Penjangkauan Mahasiswa Non Teologi Sebagai Mitra Gereja Untuk Bermisi” - Pilemon Bukit (SOTIRIA (Jurnal Theologia dan Pendidikan Agama Kristen), 2022)
Many people when they hear the word mission, immediately think of a difficult, heavy and complicated job, because mission means having to go to someone else's country. In terms of mission and mission it doesn't have to be like that. Mission and mission means going to do something, in this case proclaiming that Jesus is Lord and the savior sent by God to mankind. For this mission, a strategy is needed and an effective and efficient strategy is to serve non-theological students to know and believe in Jesus and then develop it. With them they already know and believe in Jesus, so since they became students, they have been able to make missions on campus, in boarding houses, at their parents' homes, in churches and in their hometown during their holidays and especially after they have completed their education